2003
DOI: 10.1042/bj20021224
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the SHM2 gene, encoding one of two serine hydroxymethyltransferase isoenzymes, reduces the flux from glycine to serine in Ashbya gossypii

Abstract: Riboflavin overproduction in the ascomycete Ashbya gossypii is limited by glycine, a precursor of purine biosynthesis, and therefore an indicator of glycine metabolism. Disruption of the SHM 2 gene, encoding a serine hydroxymethyltransferase, resulted in a significant increase in riboflavin productivity. Determination of the enzyme's specific activity revealed a reduction from 3 m-units/mg of protein to 0.5 m-unit/mg protein. The remaining activity was due to an isoenzyme encoded by SHM 1, which is probably mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 30 publications
0
38
0
1
Order By: Relevance
“…Overexpression of GLY1, encoding the glycine biosynthetic enzyme threonine aldolase, strongly enhanced RF production, apparently due to an improved supply of glycine, the purine precursor (312). An increase in RF production was also achieved by disruption of the SHM2 gene, encoding one of two isoenzymes of serine hydroxymethyltransferase, due to a defect in the conversion of glycine to serine, which again improved the glycine supply (398). Conversion of glyoxylate into glycine was improved by heterologous expression of the alanine:glyoxylate aminotransferase gene from S. cerevisiae (217).…”
Section: A Gossypiimentioning
confidence: 92%
“…Overexpression of GLY1, encoding the glycine biosynthetic enzyme threonine aldolase, strongly enhanced RF production, apparently due to an improved supply of glycine, the purine precursor (312). An increase in RF production was also achieved by disruption of the SHM2 gene, encoding one of two isoenzymes of serine hydroxymethyltransferase, due to a defect in the conversion of glycine to serine, which again improved the glycine supply (398). Conversion of glyoxylate into glycine was improved by heterologous expression of the alanine:glyoxylate aminotransferase gene from S. cerevisiae (217).…”
Section: A Gossypiimentioning
confidence: 92%
“…For A. gossypii, it has been shown that riboflavin production is correlated with the activity of the Rib3 protein (34). However, enhanced riboflavin overproduction has been reported only when GTP precursors are added to the medium or when the purine or glycine pathways are engineered to provide high concentrations of GTP precursors (16,21,25,35,38). This indicates that GTP availability is a limiting factor for riboflavin production in A. gossypii.…”
mentioning
confidence: 83%
“…Liquid cultures were inoculated with 1 ϫ 10 6 spores per liter of medium and were performed on a rotary shaker at 120 rpm. The determination of riboflavin production was performed by high-performance liquid chromatography as described previously (35).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The A. gossypii ATCC 10895 strain was used and was considered a wild-type strain. A. gossypii was cultured at 28°C using MA2 rich medium (8), synthetic complete medium (27), or synthetic minimal medium (26). A. gossypii transformation, genomic DNA and RNA isolation, Southern blot and Northern blot analyses, spores isolation, cell protein extraction, and determination of total riboflavin contents were carried out as previously described (24,26).…”
Section: Methodsmentioning
confidence: 99%